Studi Kapasitas Baterai 110 Vdc Pada Gardu Induk 150 KV Bangkinang - Ricky Agned; Nurhalim Nurhalim (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
PT. PLN (Persero) substation Bangkinang is central to setting the load demand of electric power, central security equipment electrical power system and the center of the normalization of the disturbances in the region Bangkinang. DC source is the heart of the electrical distribution system, in which the reliability of the source of DC was very influential to the performance of theequipment for distribution of electrical energy, especially equipment that is in substations Bangkinang integrated with the equipment that serves as the primary distributor of electricity. DCsystem consists of a rectifier which serves to AC voltage converter to a DC voltage using AC as the input source being particularly vulnerable to the threat of disruption such as loss of voltage due to an AC source of the transformer substation outages own use due to interruption of transmission or power transformer. Therefore, to reduce the impact of losses in result of these disorders requires a DC system is reliable and high stability is equipped with a backup power source is a battery that isintegrated with the rectifier. In this study will measure the per-cell voltage of 110 Vdc battery and test the battery capacity of 110 VDC substation of 150 KV Bangkinang using non-hypotheticalkomprasi convening phenomenon comparison with the standard. Based on 110 Vdc battery capacity testing of substation of 150 KV Bangkinang NiCd battery bank can be said to be reliable because itworks over IEEE standards for testing after a 5 hour battery bank has a voltage of 94 V readable on a gauge. In the measuring instrument is known by 88 V Warning Limit, and Stop Limit is 86 V.In order to maintain the stability of the rectifier to the battery charging from AC voltage supply required stable from the substation.Keywords: Rectifier , Battery , Battery Capacity of Substations.